PROTEOMIC PROFILE OF CYSTEINE OXIDATION IN VASCULAR SMOOTH MUSCLE CELLS IN HUMAN HYPERTENSION. (June 2022) - Camargo, Livia; Samji, Sheon; Lilla, Sergio; Zanivan, Sara; Bulleid, Neil; Hartley, Richard; Delles, Christian; Leiper, James; Fuller, Will; Montezano, Augusto; Touyz, Rhian
Abstract : Objective: Phenotypic switching of vascular smooth muscle cells (VSMCs) is a fundamental process in vascular dysfunction and remodeling associated with hypertension. Mechanisms underlying this process involve reactive oxygen species (ROS) and redox-dependent signaling pathways. However, the proteomic signature and effects of ROS on VSMC proteome in human hypertension are unknown. Using high fidelity proteomic analysis, we characterized the proteome of VSMC in human hypertension. Design and method: VSMC from resistance arteries from normotensive (NT) and hypertensive (HT) subjects were studied. Protein expression and cell migration were assessed by immunoblotting and wound healing assay respectively. VSMC proteins were labelled with isobaric tandem mass tags and identified by liquid chromatography tandem mass spectrometry. The oxidative proteome was assessed using stable isotope-labelled iodoacetamide to target cysteine thiols. Results: VSMCs from HT subjects exhibit reduced expression of alpha-SMA (0.05+0.01 vs NT:0.20 + 0.03, p < 0.05), increased expression of the proliferation marker, PCNA (0.162 + 0.3 vs NT:051 + 0.004, p < 0.05) and increased migration (54.68 + 2.86 vs NT:23.37 + 8.36, p < 0.05). The proteomic analysis identified 207 proteins upregulated in HT subjects (fold change> 1.5, p < 0.05). Gene ontology enrichment of upregulated proteins in HT showed that most proteins belong to extracellular space and plasma membrane compartments and were involved in biological processes such as extracellular matrix organization, immune response, proteolysis and cell proliferation. Extracellular matrix (ECM) proteins COL1A1, COL9A1, COL10A1, FBN1, FBLN1 were increased in cells from HT (fold change> 1.5, p < 0.05), suggesting a switch to a fibroblast-like phenotype in hypertension. Expression of proteins related to the interferon and IL-1beta pathways (IFIT1, IFIT2, IFIT3, MX1, MX2, ABCA1, ABCA2, IL1RAP, CD36, ICAM1) were also increased in cells from HT subjects (fold change> 1.5, p < 0.05). Considering the importance of oxidative stress in hypertension, we assessed the VSMC oxidative proteome. Results identified 130 significant cysteine-containing peptides, 88 showed increased oxidation in HT (fold change> 1.5, p < 0.05). Among the highly oxidized proteins in HT were ECM proteins, COL11A1, COL16A1, FBLN1 and FBLN2 (fold change> 1.5, p < 0.05). Conclusions: Our study provides new insights into the proteomic changes related to vascular phenotype in hypertension and highlights differentially oxidised candidate targets that may drive phenotypic switching associated with vascular injury and remodeling in hypertension.